2020
DOI: 10.1186/s12913-020-05089-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of psychiatric patients with high mortality and low medical utilization: a population-based propensity score-matched analysis

Abstract: Background: The decreased life expectancy and care costs of mental disorders could be enormous. However, research that compares mortality and utilization concurrently across the major category of mental disorders is absent. This study investigated all-cause mortality and medical utilization among patients with and without mental disorders, with an emphasis on identifying the psychiatric category of high mortality and low medical utilization. Methods: A total of 570,250 individuals identified from the 2002-2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The results show that older adults who reported internet use have lower depression levels than did those who did not use the internet, with adjustments made for Confounding factors ( 15 ). Jong-Yi Wang found that mortality and total medical expenditures per capita were significantly higher in psychiatric patients than in non-psychiatric patients by 1:1 dual propensity score matching ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that older adults who reported internet use have lower depression levels than did those who did not use the internet, with adjustments made for Confounding factors ( 15 ). Jong-Yi Wang found that mortality and total medical expenditures per capita were significantly higher in psychiatric patients than in non-psychiatric patients by 1:1 dual propensity score matching ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate in people with serious mental illness has been reported to be higher than that in people without such illness [ 3 , 4 ]; moreover, the life expectancy of people with serious mental illness is approximately 15 years shorter than that of individuals without such illness [ 5 ]. In Taiwan, individuals with serious mental illness were reported to experience higher mortality rates and healthcare expenditure than do individuals without such illness [ 6 ], and this gap appears to be increasing [ 7 ]. People with a diagnosis of serious mental illness do not appear to be benefiting from advances made in health care.…”
Section: Introductionmentioning
confidence: 99%